Peran Guru Pengabdian dalam Memotivasi Belajar Mahasantri - Fitrah Ardiansyah; Bagus Amirullah Umar (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to explore the role of service teachers (guru pengabdian) in motivating the learning of students (mahasantri) in the intensive program at the Institut Dirosat Islamiyah Al-Amien (IDIA) Prenduan for the 2022–2023 academic year. The research employed a descriptive qualitative method using data collection techniques such as observation, interviews, and documentation. The findings reveal that the presence of service teachers directly serves as a major source of motivation for students. Additionally, they provide motivation through verbal encouragement, exemplary behavior (uswah), personal approaches, and reinforcement of Islamic values in daily activities. The study also found that student motivation is supported by the availability of learning facilities and well-structured academic processes. Nevertheless, obstacles such as laziness, fatigue, and lack of awareness of learning goals remain. Thus, the active role of service teachers is essential in fostering a supportive and inspiring learning environment.